2021
DOI: 10.1039/d0fo03245j
|View full text |Cite
|
Sign up to set email alerts
|

Purple grumixama anthocyanins (Eugenia brasiliensisLam.) attenuate obesity and insulin resistance in high-fat diet mice

Abstract: The anthocyanins from the purple grumixama phenolic extract is responsible for reducing obesity and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
0
20
0
1
Order By: Relevance
“…Peroxisomal proliferator-activated receptor (PPAR) is a transcription factor activated by nuclear receptor superfamily ligands; it activates target genes and affects lipid metabolism, glucose homeostasis, cell proliferation, differentiation, apoptosis, and inflammatory responses ( Teixeira et al, 2021 ). Previous studies have confirmed that PPARs are expressed in atherosclerotic plaques, suggesting that PPARs are closely related to atherosclerosis-related mechanisms such as transcriptional regulation of pro-inflammatory genes, e.g., cytokines, chemokines, vascular endothelial cell adhesion factors, and metallostromal proteases ( Corona et al, 2014 ).…”
Section: Novel Mechanistic Insights: From Mitochondrial Dynamics To Atherosclerosismentioning
confidence: 99%
“…Peroxisomal proliferator-activated receptor (PPAR) is a transcription factor activated by nuclear receptor superfamily ligands; it activates target genes and affects lipid metabolism, glucose homeostasis, cell proliferation, differentiation, apoptosis, and inflammatory responses ( Teixeira et al, 2021 ). Previous studies have confirmed that PPARs are expressed in atherosclerotic plaques, suggesting that PPARs are closely related to atherosclerosis-related mechanisms such as transcriptional regulation of pro-inflammatory genes, e.g., cytokines, chemokines, vascular endothelial cell adhesion factors, and metallostromal proteases ( Corona et al, 2014 ).…”
Section: Novel Mechanistic Insights: From Mitochondrial Dynamics To Atherosclerosismentioning
confidence: 99%
“…1 HFD often gives rise to insulin resistance and consequently disrupts glucose metabolism. 2,3 Insulin resistance represents a reduction in insulin sensitivity and efficacy in insulin-dependent organs, including the adipose tissue, liver, and muscle. 4 The development of insulin resistance is closely associated with chronic lowgrade inflammation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although the development of modern medicine has effectively alleviated several diseases, unhealthy dietary patterns including high-fat diet (HFD), high-sugar diet, and high-calorie diet also contribute to the pathogenesis of metabolic disorder . HFD often gives rise to insulin resistance and consequently disrupts glucose metabolism. , Insulin resistance represents a reduction in insulin sensitivity and efficacy in insulin-dependent organs, including the adipose tissue, liver, and muscle . The development of insulin resistance is closely associated with chronic low-grade inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AÇÃO BIOLÓGICA DA LARANJA Diversos mecanismos estão relacionados as propriedades biológicas dos polifenóis na promoção à saúde, incluindo a modulação de enzimas do sistema antioxidante (Anhê et al 2015;Diaz-Rubio et al, 2015), da via de sinalização inflamatória, regulação de genes do metabolismo lipídico, da lipogênese de novo, da oxidação de ácidos graxos, redução no acúmulo de triglicerídeo hepático (Shimoda et al, 2009 ;Anhê et al, 2017;Song et al, 2016), controle da glicemia e melhora na sensibilidade a insulina e melhora da tolerância a glicose (Aranaz et al, 2019;Teixeira et al, 2021).…”
Section: Citrus Sinensisunclassified